HUBUNGAN BERAT BADAN LAHIR DENGAN KEJADIAN STUNTING PADA BALITA DI RW 01 KELURAHAN RAWA BUNGA - Nova Indriyani (2021)
Stunting is the condition of a child with a height that is not in accordance with his age. There are 3 main factors that cause stunting, namely unbalanced food intake, low birth weight (LBW) and a history of disease. The research design used was observational quantitative with a cross sectional approach. The sampling of the research used a total sampling of 89 respondents. Data was collected through a paper questionnaire consisting of birth weight, stunting incidence, mother's education, mother's age, mother's occupation, and gender of the child. The results of the chi-square analysis test obtained P value of 0.001 < (0.05) which means that there is a relationship between birth weight with the incidence of stunting in RW 01, Rawa Bunga sub-district. Suggestions for further researchers to conduct research by analyzing the relationship related to birth weight of toddlers.